Assessment of the successfulness of mangrove plantation program through the use of open source software and freely available satellite - ILYAS NURSAMSI; WULAN RATNA KOMALA (Nusantara Bioscience, 2017)
Nursamsi I, Komala WR.2017. Assessment of the successfulness of mangrove plantation program through the use of open source software and freely available satellite images. Nusantara Bioscience 9: 251-259. Mangrove forest has a major role in the process of human-environment interaction, but almost every mangrove forest in the world is under threat. In Indonesia alone, 25% of South East Asiaâ€™s mangroves are at a risk. The continued decline in mangrove forest induced by anthropogenic activity has made all the stakeholders who have the concern at the mangrove forest preservation worried, including the government. There were several programs have been performed by the government to preserve the mangrove forest. One of the programs was â€œMangrove Rehabilitation Program in three districts: Ciamis, Indramayu, and Subangâ€ held by Forestry Department of West Java Province in 2007. The aims of this study were to assess the changes in mangrove forest area before the program performed and to evaluate the successfulness of the program, using the increasing of mangrove forest area as a parameter. This study was conducted only in Subang and Indramayu Districts of West Java, Indonesia. The assessment was conducted using Landsat 4-5 TM, Landsat 7 ETM+, and Landsat 8 OLI acquired in 1996, 2006, and 2016 respectively. For each image, a supervised classification method was performed using open source GRASS GIS software. The resulting maps were then compared to quantify the changes. Field work activity conducted and confirmed the changes that occurred in the study areas. Our study shows that all of the two districts exhibit successfulness of the plantation program. Ground truth survey confirmed that the successfulness of the plantation program is due to the participation of communities in the area of study. This study also shows that by using open source software and freely available satellite images, the fast, robust, and reliable data as an initial step to monitor both short-term and long-term plantation program can be collected effectively and inexpensively.